2019
DOI: 10.3390/ijms20205131
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to High-Intensity Light Systemically Induces Micro-Transcriptomic Changes in Arabidopsis thaliana Roots

Abstract: In full sunlight, plants often experience a light intensity exceeding their photosynthetic capacity and causing the activation of a set of photoprotective mechanisms. Numerous reports have explained, on the molecular level, how plants cope with light stress locally in photosynthesizing leaves; however, the response of below-ground organs to above-ground perceived light stress is still largely unknown. Since small RNAs are potent integrators of multiple processes including stress responses, here, we focus on ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…Transcriptome analysis of leaves of rapeseed seedlings exposed to HL stress for 16 h revealed 7390 DEGs ( Figure 2 ), indicating a considerable change in gene expression under HL stress as observed in other plant species like Panax ginseng , A. thaliana and Begonia semperflorens [ 66 , 67 , 68 ]. Furthermore, GO analysis demonstrated that many GO terms related to photosynthesis were most enriched with DEGs ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 71%
“…Transcriptome analysis of leaves of rapeseed seedlings exposed to HL stress for 16 h revealed 7390 DEGs ( Figure 2 ), indicating a considerable change in gene expression under HL stress as observed in other plant species like Panax ginseng , A. thaliana and Begonia semperflorens [ 66 , 67 , 68 ]. Furthermore, GO analysis demonstrated that many GO terms related to photosynthesis were most enriched with DEGs ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 71%
“…Since miRNAs are thought to influence circadian controlled processes ( 55 , 56 ) and are common in coding regions, we tested the possibility that these k -mers could represent miRNAs by aligning them (plus the surrounding sequence) to mature ath-miRNA sequences to identify matches (see Materials and Methods ). Two of the four k- mers matched miRNA sequences that were associated with developmental timing ( 57 ) and chloroplast biogenesis ( 58 ). Therefore, for a subset of transcripts, the k -mers could represent putative miRNA binding sites that have been experimentally linked to circadian, regulated processes, although this only accounts for a small proportion of the transcripts ( SI Appendix , Table S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Since miRNAs are thought to influence circadian controlled processes [46,47] and are common in coding regions, we tested the possibility that these k -mers could represent miRNAs by aligning them (plus surrounding sequence) to mature ath-miRNA sequences to identify possible matches (see Methods). Two of the four k- mers and their flanking sequence matched miRNA sequences that were associated with developmental timing [48] and chloroplast biogenesis [49]. Therefore, for a subset of transcripts, the k -mers could represent putative miRNA binding sites that have been experimentally linked to circadian regulated processes, although this only accounts for a small proportion of the transcripts (Table S5).…”
Section: Resultsmentioning
confidence: 99%